Identification of specific integrin cross-talk for dermal fibroblast cell adhesion using a mixed peptide-chitosan matrix. (February 2019) - Hozumi, Kentaro; Teranishi, Yui; Enomoto, Sayaka; Katagiri, Fumihiko; Kikkawa, Yamato; Nomizu, Motoyoshi
Extracellular matrix molecules are recognized by several integrin subtypes, making identification of cross-talk among different integrin subtypes difficult. Here, we evaluated the cross-talk of integrin subtypes using four different integrin-binding peptides (FIB1; integrin αvβ3/α5β1, A2G10; integrin α6β1, EF1zz; integrin α2β1, or 531; integrin α3β1) derived from extracellular matrix molecules. Various combinations of two different integrin-binding peptides were mixed and conjugated on a chitosan matrix at various molar ratios and were evaluated for cell attachment activity. FIB1/A2G10 (molar ratio 5:5; total 10 nmol/well)-chitosan matrix significantly enhanced cell attachment activity compared with sum of the cell attachment activity on FIB1 (5 nmol/well)-chitosan matrices and A2G10 (5 nmol/well)-chitosan matrices, respectively. However, none of the other peptides showed a significant activity change when they were mixed and conjugated on a chitosan matrix. We investigated the mechanisms of this enhancement. FIB1/A2G10 (8:2 or 6:4)-chitosan matrix increased the cell spreading, phosphorylation of focal adhesion kinase at Y397, and slightly decreased phosphorylation of caveolin-1 at Y14 in fibroblasts compared with FIB1-chitosan and A2G10-chitosan matrices. These results indicate that FIB1/A2G10 (8:2 or 6:4)-chitosan matrix synergistically enhances cell attachment, suggesting that integrins αvβ3/α5β1 and α6β1 are involved in a cross-talk and synergistically enhance cell attachment. These findings also suggest that the mixed peptide-chitosan matrix system can regulate the ratio of two different peptides and is useful for evaluating cellular functions through receptor-specific cross-talk. Further, FIB1/A2G10 (8:2 or 6:4)-chitosan matrix could be a useful material for tissue engineering.